2008
DOI: 10.1021/ja801058h
|View full text |Cite
|
Sign up to set email alerts
|

Artificial DNA Made Exclusively of Nonnatural C-Nucleosides with Four Types of Nonnatural Bases

Abstract: Abstract:We describe a new class of DNA-like oligomers made exclusively of nonnatural, stable C-nucleosides. The nucleosides comprise four types of nonnatural bases attached to a deoxyribose through an acetylene bond with the -configuration. The artificial DNA forms right-handed duplexes and triplexes with the complementary artificial DNA. The hybridization occurs spontaneously and sequence-selectively, and the resulting duplexes have thermal stabilities very close to those of natural duplexes. The artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 102 publications
1
53
0
1
Order By: Relevance
“…Other research groups have recently adopted an enlargedbase-pair strategy as well. 14-16 In our approach, benzopyrimidines pair with purines and benzopurines 17 with pyrimidines, yielding up to eight letters of information encoding capability. 5,7 The study of this nonnatural genetic set gives basic insight into the chemical, structural, and biophysical properties that govern encoding and transmission of genetic information.…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups have recently adopted an enlargedbase-pair strategy as well. 14-16 In our approach, benzopyrimidines pair with purines and benzopurines 17 with pyrimidines, yielding up to eight letters of information encoding capability. 5,7 The study of this nonnatural genetic set gives basic insight into the chemical, structural, and biophysical properties that govern encoding and transmission of genetic information.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of new DNA-like genetic architectures have been described, including base pairs with four hydrogen bonds 46 and bases with ethynyl homologation. 47 Although such fully unnatural designs might generally be expected to interact with natural enzymes poorly, experiments show that this might not always be the case. For example, our laboratory demonstrated that xDNA can be replicated in vitro by some DNA polymerases.…”
Section: Synthetic Biologymentioning
confidence: 99%
“…Taking a related expanded-size approach, Inouye has recently designed an artificial genetic set composed entirely of nonnatural C-glycosides in which added length is conferred by an ethynyl group [59]. The recognition of these bases relies on six-member heterocycles with Watson-Crick-like hydrogen-bonding faces (iG*:iC*, three hydrogen bonds, A*:T* two hydrogen bonds), linked to the C1′ of deoxyribose by the ethynyl spacer.…”
Section: Why Modify Dna Bases?mentioning
confidence: 99%